The Effect of the Use of Knee Support to Knee Pain of Skateboard Players in Singaraja Bali - Rachmat, Nur; Putra, Aji (Poltekkes Kemenkes Jakarta I, 2022)
Background: Skateboarding is also an extreme sport and in Indonesia it is not very popular but has the potential to be liked by young people in Singaraja Bali. Due to the nature of skateboarding, including high speeds and extreme maneuvers, such as jumping from heights and performing extreme movements that can injure the joint bearing of the knee, injuries often occur when a skateboarder collides with an inanimate object, falling off the skateboard. Knee support is made of elastic material with medial and lateral supports made of metal. Elastic material that has the ability to stretch and return to its original state quickly so that it serves as a fixation on the knee that suffers from knee pain. With the fixation on the knee as well as support and stabilizer on the knee joint will relieve pain in patients with knee pain so it is expected to reduce pain. Method: The research design of the effect of the use of knee support to knee pain of skateboard players is a type of quantitative research using a quasi-experimental design with one group pre and posttest design. Data was collected in the Singaraja Bali sports hall in September - December 2020. Skateboarders' knee pain was measured using a VAS (Visual Analogue Scale) questionnaire. The population is 14 skateboarders who play at the Singaraja Bali sports hall. All respondents were sampled using the total sampling method. Result: There were 11 males and 3 females as respondents. Pre-test Knee pain VAS score before using knee support is average of 5.93 while the post test score after using knee support for two weeks is average of 2.14. Normality data using the Shapiro Wilk result is not normally distributed. The result of Wilcoxon is p value 0.001. P value is less than 0.05. So it can be concluded that the use of knee support has a significant effect in reducing knee pain in skateboarders. Conclusion: there is an effect of the use of knee support to knee pain of skateboard players. It is advisable for skateboarders to wear knee support when feeling pain while skateboarding.